PENERAPAN METODE SINGLE MOVING AVERAGE DAN EXSPONENTIAL SMOOTHING PADA USAHA ASRIE MODESTA - Mila fitriani; Dirarini Sudarwadi Sudarwadi; Nurlaela Nurlaela (Cakrawala Management Business Journal, 2020)
This study aims to (1) analyze the number of demands for batik products in the second period of 2018. (2) To analyze the most appropriate forecasting method. (3) To analyze the forecasting of the first period in 2019 using the selected forecasting method. This reseach uses primary data and secondary data with data collection techniques using interviews, observation, and documentation. The analysis used is Single Moving Averages and Exsponential Smoothing. The results of research in forecasting demand for batik products in 2019 with the Single Moving Average method are 3,936 units with Mean Absolute Deviation (MAD) of 632.5 units and Mean Square Error (MSE) of 693,718 units. And the Exsponential Smoothing Alpha 0.05 method is 2,788,879 units, with Mean Absolute Deviation (MAD) of 694,318 units and Mean Square Error (MSE) of 960,665 units. The method suggested to company in making forecast predictions is to use the Single Moving Averages method because it has the smallest error rate that compared to the Exsponential Smoothing method with an Alpha value of 0.05.